DISEMINASI IBU PKK DUSUN KALLIMPO DALAM MENGOLAH LIMBAH KULIT PISANG MENJADI BIO-BATERAI ENERGI MASA DEPAN - Andi Nurannisa; Andi Muhammad Irfan Taufan Asfar; Andi Muhammad Iqbal Akbar Asfar; Sartika Sari Dewi (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
Batteries are one source of electrical energy that is still an important need in everyday life. However, battery waste contains hazardous and toxic chemicals that require proper handling to deal with it. One of them is by procuring alternative batteries that are more environmentally friendly by utilizing banana peel. Banana peel has a content that can be ionized and conduct electricity, so it is appropriate to be used as an electrolyte paste that has optimum battery life. Processing of banana peel waste into an alternative battery (bio-battery) was carried out by PKK Dusun Kallimpo through three stages, namely socialization, training and monitoring. This service program provides supplies to partners in overcoming battery needs through their own production to reduce the cost of purchasing batteries, and can be an update for science and technology as the forerunner of future energy, so that partners are able to create prosperous and competitive families..